Wartime interest rate pass-through in Ukraine: The role of prudential indicators - Anton Grui (Charles University in Prague, Institute of Economic Studies (IES), 2024)
In this paper, I study Ukraine's heterogeneous and time-variant pass-through from the money market interest rate to bank deposit and lending rates. I utilize a new panel dataset containing individual banks' characteristics and prudential indicators over 2019-2023, a period comprising the full-scale Russian invasion. First, using TVPARDL models, I reveal that during the invasion, the pass-through diminished for all examined bank products. It is also weaker to deposits in times of monetary policy tightening. Second, using panel regressions, I show how banks' characteristics and prudential indicators influence the transmission. Their impacts are asymmetric during monetary policy tightening and loosening. Overall, I track wartime interest rate pass-through for practical monetary policy purposes and contribute to the topic of interactions between monetary and prudential policies.
Keywords: C54; E43; E52; G21; 330; monetary policy transmission mechanism; interest rate pass-through; wartime economy